Platelet-rich plasma (PRP) and tendon healing: comparison between fresh and frozen-thawed PRP. (17th February 2020) - Kaux, Jean-François; Libertiaux, Vincent; Dupont, Laura; Colige, Alain; Denoël, Vincent; Lecut, Christelle; Hego, Alexandre; Gustin, Maxime; Duwez, Luc; Oury, Cécile; Gothot, André; Greimers, Laura; et al.
Abstract: Platelet-rich plasma (PRP) is increasingly used in the treatment of musculoskeletal diseases. Its preservation by freezing it for the realization of multiple injections in clinical use has never been discussed. Calcaneal tendons of rats were surgically sectioned. Platelet concentration of the PRP was 2.5 x 10 6 /µl with autologous plasma of rats. Frozen-thawed PRP was prepared by performing two cycles of freezing and thawing on PRP aliquots. Both platelet preparations were injected in the lesion. Biomechanical and histological evaluations were carried out after 7, 20 or 40 days post surgery. After 7 and 40 days, no significant difference was observed between the PRP and the frozen-thawed PRP group. There is however a difference 20 days after surgery: the ultimate tensile strength (UTS) was greater in the fresh PRP group. No obvious difference with histological aspect was observed between the two groups. In conclusion, fresh PRP and frozen-thawed PRP injections can lead to similar results in the healing process of section calcaneal tendons of rats. Improvements with fresh PRP are slight. PRP could thus be frozen to be preserved if multiple injections are needed (e.g. osteoarthritis).